Avaliação da contribuição do Programa Mais Educação para escolas municipais de Rio Verde-GO : dos números do Ideb à percepção qualitativa dos sujeitos - Moreira, Sebastiana Aparecida (2013)
This study aimed to evaluate the performance of More Education Program in the city of Rio Verde, State of Goiás, and based on the results, contribute to the construction of knowledge about the big challenge of improving the quality of basic public education in Brazil. Permeated by the analysis of concept of integral education consubstantiated, mainly, by the work of Anísio Teixeira, studied the principles and strategies of More Education Program, as well as large-scale evaluation and Ideb, the main indicator for assessing the quality of Brazilian schools. The full-time school theme had as a basic reference the work of Jacqueline Moll and Vitor Paro. Were analyzed the performance of schools in Rio Verde Ideb, before and after the implementation of More Education Program. We compared the performance of schools in Ideb, with and without the program within a period of four years. Moreover, questionnaires were administered and interviews with students, monitors, teachers, coordinators and managers of schools that had implemented the More Education Program. The results evidenced that in the context of schools in Rio Verde, GO, The More Education Program is achieving its objectives and especially, has contributed to the improvement of learning and withdrawal of children, youth and vulnerable adolescents in situations of risk